Implementation of Science in the Discipline of Worship for People with Visual Sensory Disabilities: Implementasi Sains dalam Kedisiplinan Beribadah Penyandang Disabilitas Sensorik Netra - Saputro, Anip Dwi; Nuraini; Rois, Adib Khusnul (Halaqa: Islamic Education Journal, 2023)
People with sensory-blind disabilities need assistive devices to support their independence in everyday life. One of the tools to find out the time, place, and activities of worship. This article aims to find out the implementation of science in the discipline of worship for blind people at the LKS Tunanetra 'Aisyiyah Ponorogo. This article uses a qualitative descriptive method by collecting data and describing it thoroughly. Sources of data in this study included primary data, namely interviews with the head of the LKS, deputy head of the LKS for parenting, caregivers, companions, and foster children with disabilities, and secondary data sources in the form of observations and institutional documents needed in this study. The results of the study show that the implementation of the discipline of worship is carried out starting from the planning of disability services, the implementation of disability services, and the evaluation of the implementation of disability services, especially the discipline of worship. The impact of the implementation of science on the discipline of worship shows that the discipline of worship can also be programmed and well-controlled according to the parenting service program for persons with disab.